2009
DOI: 10.1200/jco.2008.20.8876
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Prostate Tumor Angiogenesis and Cancer-Specific Mortality in the Health Professionals Follow-Up Study

Abstract: A B S T R A C T PurposeTumor growth requires the development of independent vascular networks that are often primitive in morphology and function. We examined whether microvessel morphology contributes to the considerable biologic heterogeneity of prostate cancer. MethodsWe evaluated microvessel morphology as a predictor of prostate cancer mortality among 572 men in the Health Professionals Follow-Up Study diagnosed with cancer during 1986 to 2000. We immunostained prostatectomy tumor block sections for endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 27 publications
4
98
0
2
Order By: Relevance
“…Increased MVD has also been described as a negative prognostic factor in solid tumors but has not been explored in DLBCL treated with R-CT. 13 The prognostic value of the MVD in our study agrees with previously published GEP data on DLBCL. 2 The gene expression signatures 'stromal 1' and 'stromal 2', related to extracellular matrix and angiogenesis-related genes, respectively, were synergistic in predicting survival.…”
Section: Discussionsupporting
confidence: 82%
“…Increased MVD has also been described as a negative prognostic factor in solid tumors but has not been explored in DLBCL treated with R-CT. 13 The prognostic value of the MVD in our study agrees with previously published GEP data on DLBCL. 2 The gene expression signatures 'stromal 1' and 'stromal 2', related to extracellular matrix and angiogenesis-related genes, respectively, were synergistic in predicting survival.…”
Section: Discussionsupporting
confidence: 82%
“…The influence of metabolic factors may further need a relatively well-differentiated target tissue for their action. T2DM and long-term hyperglycemia frequently results in microvascular complications due to capillary dysfunction and altered shape and size of intraprostatic microvessels have been linked to the risk of lethal prostate cancer (39). Decreased microcirculation might thus alternatively explain the reduced risk among men with T2DM (40).…”
Section: High-and Low-risk Tumorsmentioning
confidence: 99%
“…And it has been reported that microvessel density, a measurement of prostate cancer angiogenesis, has been shown to be a predictor of metastasis and survival (Weidner et al, 1993). It is shown that that the microvessel density in prostate cancer tissues is significantly higher than normal prostate, and the microvessel density in metastatic prostate cancer is higher than that in nonmetastatic cancer (Brawer et al, 1994;Mucci et al, 2009;Aragon-Ching et al, 2010). Thus, targeting angiogenesis has been the subject of several clinical investigations.…”
Section: Discussionmentioning
confidence: 99%